Seize the Moment : America's Challenge in a One-Superpower World - Nixon, Richard (New York Simon & Schuster, 1992)
The former president defines the future challenges facing America as the Cold War ends, Communism collapses, and new opportunities open up in the world of international politics.
Include Index
Keywords: United States -- Diplomatic Relations